Impact of the COVID-19 Pandemic on Behavioral and Emotional Factors in Pediatric Patients with Headache - Hey-Joon Son; Joo-Ok Jin; Kon-Hee Lee (Korean Child Neurology Society, 2024)
Purpose Headaches are common in childhood and adolescence and are often exacerbated by various triggers. The coronavirus disease 2019 (COVID-19) pandemic has profoundly altered daily life worldwide. In this study, we investigated potential behavioral and emotional changes among pediatric patients with headaches, treated either before or after the onset of the COVID-19 pandemic. Methods We examined 162 patients who visited our pediatric headache clinic between March 2018 and August 2021. The study included patients with primary headaches who completed a questionnaire assessing behavioral and psychiatric characteristics. We reviewed their clinical features, imaging studies, and scores on the Korean Child Behavior Checklist (K-CBCL), State Anxiety Inventory for Children (SAIC), Trait Anxiety Inventory for Children, and Children's Depression Inventory (CDI). Statistical analysis was conducted using the Mann-Whitney U test, among other methods. Results The 162 patients (mean age, 11.7±3.3 years) were classified based on whether they visited before (n=81) or after (n=81) the onset of the COVID-19 pandemic. The average CDI and SAIC scores were significantly higher in those who presented after pandemic onset. In this group, the odds ratio for an abnormal CDI score was 4.971. A weak positive correlation was found between the CDI score and the K-CBCL total problem score, with a correlation coefficient of 0.297. Conclusion Pediatric patients visiting the headache clinic after the onset of the COVID-19 pandemic exhibited significantly higher levels of anxiety and depression compared to pre-pandemic visitors. Recognizing the considerable impact of the pandemic may help inform the management of pediatric headaches.